Influence of sprouting and elicitation on phenolic acids profile and antioxidant activity of wheat seedlings. (July 2016) - Gawlik-Dziki, Urszula; Dziki, Dariusz; Nowak, Renata; Świeca, Michał; Olech, Marta; Pietrzak, Wioletta
Abstract: Influence of germination and elicitation on nutraceutical potential of sprouted wheat was investigated. The seeds of three Polish winter wheat cultivars were elicited with 0.1% (w/v) of Saccacharomyces cerevisiae (SC) extract, 0.1% (v/v) Salix daphnoides (SD) bark extract and their combinations (SC/SD 1:1). Seeds were germinated for 4 day at 20 °C in darkness. For phenolic acids determination LC-ESI-MS/MS analysis was used. Antiradical ability, chelating power, reducing power and ability to prevent lipids against oxidation were determined. Bioaccessibility of antioxidative compounds was estimated using in vitro digestion method. Eleven phenolic acids (protocatechuic, p -hydroxybenzoic, vanillic, caffeic, syryngic, p -coumaric, cis - and trans- ferulic, salicylic, trans- and cis- synapinic) were identified. Sprouting increased p -hydroxybenzoic, syryngic and p -coumaric acids level. The most effective elicitor for improving antioxidant activity of potentially bioaccessible phytochemicals was SD. Especially high effect was obtained for antiradical activity, chelating power and ability to lipid prevention. Highlights: Phenolic acids profile and antioxidant activity of sprouted wheat was studied. Sprouting increased p -hydroxybenzoic, syryngic and p -coumaric acids level. Antioxidant potential of sprouted wheat was enhanced by natural elicitors.